Cultivating the democratic mind - Ripatti-Torniainen, Leena (Javnost (Ljubljana), 2011)
The article analyses formative texts of public journalism, written in the USA in the 1990s, by constructing comparisons to adult education. The article initially introduces the rationale of paralleling public journalism with adult education by discussing the congruence of aims, methods, and definitions of professional roles between public journalism and American pragmatist adult education. The authors use the methods of intellectual history to analyse the intervention in the public conduct of citizens, which the leading early proponents of public journalism, Jay Rosen and Davis Merritt, constructed. The article demonstrates that Rosen and Merritt's idea of intervention consists of two distinct elements. First, Rosenand Merritt urge journalists to animate social association and thus create prerequisites for citizens to recognise their public and political agency. Second, they suggest journalists to promote inclusive and solution-oriented public discussion among the citizenry. Adult education recognises both elements, yet the purpose Rosen and Merritt articulate for intervention is abstract and instrumental, compared to adult educational purposes, and their view on citizen empowerment is more restricted. The abstract ideal of public life, as opposed to the emancipation of persons, is at the centre of Rosen and Merritt's argument.
Keywords: izobraževanje odraslih; mass media; množični mediji; novinarstvo; journalism; United States of America; ZDA